Architecture in Contemporary Literature - Erdoan, Nevnihal; Temel Akarsu, Hikmet (Bentham Science Publishers, 2023)
Architecture in Contemporary Literature artfully weaves the tapestry of architecture with the eloquence of modern literary masterpieces. In this follow up to their earlier work on architecture in fictional literature, the editors have carefully selected 31 significant works from contemporary world literature, offering a fresh educational approach to literary critique and architecture. This exploration allows readers to perceive life through the lens of architectural backgrounds. Nature, society, humans, and cities come to life through these chosen literary gems. Extensive collaboration with architects, intellectuals, academics, writers, and thinkers culminates in the selection of influential works that guide present-day architectural perspectives and aspirations. The book promises to be a valuable reference for undergraduate and graduate students in architecture, interior architecture, urban planning, fine arts, humanities, social sciences, and various design disciplines. Yet, its appeal also extends to anyone with an appreciation for urban life and a desire for a broader understanding of the intricacies of architecture. Whether you're an expert in design, culture, art, sociology, or literature, or simply an avid learner, Architecture in Contemporary Literature is a compelling exploration that deserves a prominent place on your bookshelf. Engage with its pages and immerse yourself in the fusion of architectural insight and literary artistry.